Institutions and institutional change: rethinking the ‘resource curse’ from the news institutionalisms and the Peruvian experience - Orihuela, José Carlos (2013)
The "resource curse" is a term that refers to a heterogeneous set of theories about why natural resource abundance undermines the path of a political economy. For each type of "curse", we argue that moving from asking "why" to consider "how" and "when" it permits a more refined conceptual and empirical approach to the link between natural resources and social change, be it economic or political development. Specifically, the micro study of actors and institutions in historical context sheds light on areas where aggregate macro statistical study cannot provide. To do this, the critical use of the conceptual frameworks of the new institutionalism in the social sciences enhances the depth of empirical research. The contemporary Peruvian experience shows the variety and variability of economic and political challenges of development based in resources.